About FairTax - Åsa Gunnarsson; Danuše Nerudová; Margit Schratzenstaller (Intereconomics, 2019)
Our research shows that in the ongoing discussion concerning 'the social dimension of Europe', it appears that there is much to gain if the tax policy interaction between Member States and the European Union, which is currently taking place within the European Semester, could be extended to consider that taxes are one of the most efficient instruments to achieve social and welfare policy outcomes.
Keywords: 330